2019
DOI: 10.1136/bmjopen-2019-031085
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of depressive symptoms among gay, bisexual and other men who have sex with men in the PROUD randomised clinical trial of HIV pre-exposure prophylaxis

Abstract: ObjectivesThe aim of this analysis is to: (i) assess the prevalence of clinically significant depressive symptoms at baseline and follow-up for participants in the PROUD trial of HIV pre-exposure prophylaxis (PrEP), examining changes in prevalence over time and (ii) investigate the association of socioeconomic and psychosocial factors with depression.MethodsPROUD was an open label randomised trial evaluating the benefit of PrEP for 544 HIV-negative gay, bisexual and other men who have sex with men (GBMSM) in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
3
1
Order By: Relevance
“…However, surprisingly, the percentage of individuals with depressive symptoms was very low in our study, especially if compared with another study in which 28.3% of participants had moderate–severe depression 36 . Anxiety and depression rates might be higher in MSM than in heterosexual men, in relation to the discrimination and social stigma linked to their sexual orientation and drug use 37 . In addition, our study demonstrated that anxiety, but no depressive symptoms, was more frequent in the chemsex group, certainly due to the low number of participants with signs of depression.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…However, surprisingly, the percentage of individuals with depressive symptoms was very low in our study, especially if compared with another study in which 28.3% of participants had moderate–severe depression 36 . Anxiety and depression rates might be higher in MSM than in heterosexual men, in relation to the discrimination and social stigma linked to their sexual orientation and drug use 37 . In addition, our study demonstrated that anxiety, but no depressive symptoms, was more frequent in the chemsex group, certainly due to the low number of participants with signs of depression.…”
Section: Discussioncontrasting
confidence: 86%
“…36 Anxiety and depression rates might be higher in MSM than in heterosexual men, in relation to the discrimination and social stigma linked to their sexual orientation and drug use. 37 In addition, our study demonstrated that anxiety, but no depressive symptoms, was more frequent in the chemsex group, certainly due to the low number of participants with signs of depression. Nevertheless, the link between chemsex, anxiety, and depression is still unclear due to the presence of many confounding factors, including the effects of PS and the presence of these symptoms before chemsex practices, which could favor PS use.…”
Section: Discussionmentioning
confidence: 59%
“…In our study of stigma and mental health among GBM who use PrEP, we found that nearly half of the study participants (48%) endorsed some depression symptoms and that 47% endorsed some anxiety symptoms, whereas 15% reported moderate-severe depression and 9% reported moderate-severe anxiety. In the general population in Guatemala, there is a 3.7% and 4.2% estimated PREEXPOSURE PROPHYLAXIS STIGMA AND MENTAL HEALTH prevalence of depression and anxiety, respectively (World Health Organization, 2017); these relative disparities between the prevalence of depression and anxiety among GBM versus the general population are similar to those reported in other countries (Cochran et al, 2003;Miltz et al, 2019).…”
Section: Discussionsupporting
confidence: 62%
“…MSM on PrEP who reported poly‐drug use and depression were significantly more likely to report receptive condomless anal intercourse than those who only reported poly‐drug use or only reported depression at baseline assessment [84]. Conversely, among gay and bisexual MSM receiving PrEP in the United Kingdom, despite increased depressive symptoms over time, neither depressive symptoms nor interpersonal violence were associated with sexual risk behaviours [85,86].…”
Section: Resultsmentioning
confidence: 99%